Atividades de Matemática Financeira por meio de aprendizagem coletiva nos anos finais do ensino fundamental - Oliveira, Juliana Bauer de (Universidade Federal de São Carlos, 2016)
We present in this research a proposal about our practice within the classes of Financial Education Experiences, as part of the pedagogical project for a full - time education of the SESI - SP network, with a researcher’s view of the activities proposed to the students. The proposal of Integral Education in Full Time means a break in the vision of the fragmented curriculum, producing curricular guidelines that aim at the integration of the components of a basic curriculum with a diversified part. The subjects that fulfill this role were called, by the SESI-SP network, Experiences, aiming at the incorporation of new professional profiles, new knowledge, with a transdisciplinary view. As part of the curriculum of Integral Time classes of eighth and ninth grade, we taught two weekly classes of Financial Education Experiences. This survey involved one hundred and seventy-six students in classes that occurred in the morning and afternoon. In order to propose a differentiated practice, we use financial mathematics activities through collective learning at the Elementary level, taking into account the context of the young people, their dealings with money, their relation to consumption, their influence on future achievements, and also the importance of personal and family planning. The activities were planned based on the study of fractional and decimal rational numbers, percentages, proportionality, besides working concepts of the area of magnitudes and measures. We were able to see a significant increase in the overall average of the ratings scores. We believe that this improvement is a result of the greater participation of the students in the classes, mainly of students more agitated, generating less indiscipline. Students became aware that instead of making debts that they cannot pay later, it would be best if they were scheduled to purchase a product later, without the need to pay interest.
Activities of Financial Mathematics by means of collective learniing in the final years of fundamental teaching
Keywords: Educação Financeira; Matemática; Financial education; Mathematic; CIENCIAS EXATAS E DA TERRA::MATEMATICA